Caring for hospitalized breastfeeding mothers and children - Melissa Bartick; Jordan Lim; Liliana Simon; Sarah E. Dodd (Journal of Hospital Medicine, 2026)
Abstract Breastfeeding mothers and children are occasionally hospitalized. Continuing breastfeeding during hospitalization and beyond is important for the health outcomes and well‐being of mother and child. Breastfeeding in the hospital is associated with better hospital outcomes for children. However, breastfeeding can be challenging during hospitalization, particularly due to mother–infant separation and unfamiliarity by members of the treatment team with important aspects of breastfeeding. Hospitalization may result in unintended cessation of breastfeeding, which can also cause maternal emotional distress. Hospitals treating women of childbearing age and/or children should have a written policy that minimizes separation and provides knowledgeable breastfeeding/lactation‐specific resources and support.